Desarrollo de video juego para la estimulación cognitiva de personas con accidentes cerebrovasculares (2023)
This research was conducted in order to design a 2D video game with Unity programming for the rehabilitation of attention, memory and concentration of people in general, which would help in the problem of limited access to this type of therapy due to the high costs required for a medical psychotherapeutic process, which is not included in the POS of the health system in Colombia. So that this study is distributed in 5 chapters, the first refers to the introduction in which reference is made to the main cognitive difficulties that can be stimulated by means of this type of tools, in the second chapter is the objectives of the research, which is to design a non-immersive 2D video game in order to help in the process of cognitive rehabilitation of people, the next chapter is the theoretical framework where the theoretical foundation of both cognitive analysis and technical knowledge of video games is found, in a fourth chapter is the descriptive and quantitative research methodology, with an empirical